2023
DOI: 10.1093/jee/toad036
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative analysis of 3 pollen sterilization methods for feeding bumble bees

Abstract: Pollen is an essential component of bee diets, and rearing bumble bees (Bombus spp.) for commercial use necessitates feeding pollen in mass quantities. This pollen is collected from honey bee (Apis mellifera L.) colonies because neither an artificial diet nor an economical, large-scale pollen collection process from flowers is available. The provenance of honey bee-collected pollen is often unknown, and in some cases has crossed international borders. Both deformed wing virus (DWV) and the fungal pathogen Asco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Gamma and e-beam irradiation do inactivate the honey bee pathogens P. larvae , A. apis , N. ceranae , and viruses ( Hornitzky 1994 , Melathopoulos et al 2004 , Simone-Finstrom et al 2018 , Strange et al 2023 ). As treatment for American foulbrood commonly uses a dose of 10 kGy, there is an opportunity to increase that dose to 35 kGy to achieve control of viruses; however, the potential benefits and costs to colony health should be better studied before recommendations are made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma and e-beam irradiation do inactivate the honey bee pathogens P. larvae , A. apis , N. ceranae , and viruses ( Hornitzky 1994 , Melathopoulos et al 2004 , Simone-Finstrom et al 2018 , Strange et al 2023 ). As treatment for American foulbrood commonly uses a dose of 10 kGy, there is an opportunity to increase that dose to 35 kGy to achieve control of viruses; however, the potential benefits and costs to colony health should be better studied before recommendations are made.…”
Section: Discussionmentioning
confidence: 99%
“…As treatment for American foulbrood commonly uses a dose of 10 kGy, there is an opportunity to increase that dose to 35 kGy to achieve control of viruses; however, the potential benefits and costs to colony health should be better studied before recommendations are made. Moreover, the type of sample treated by irradiation could influence the efficacy against viruses, as DWV-contaminated pollen treated with ~30 kGy gamma irradiation did not have lower DWV levels posttreatment compared to untreated pollen ( Strange et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies found that larvae acquire fatty and amino acids from microbial prey within provisions, resulting in heavier bees than those reared on sterile pollen [12][13][14]. These opposing results may be explained by differences in pollen sterilization methods: in choice assays, EO exposure does not affect the palatability of pollen to bumblebees [28], but it is unknown whether soaking provisions in ethanol [12][13][14] affects pollen consumption in solitary bees, perhaps leading to differences in biomass, fat content, and trophic positions. Of note, while not statistically significant, bumblebees consumed less pollen per day when fed EO exposed pollen compared to the no treatment control [28].…”
Section: Discussionmentioning
confidence: 99%
“…These opposing results may be explained by differences in pollen sterilization methods: in choice assays, EO exposure does not affect the palatability of pollen to bumblebees [28], but it is unknown whether soaking provisions in ethanol [12][13][14] affects pollen consumption in solitary bees, perhaps leading to differences in biomass, fat content, and trophic positions. Of note, while not statistically significant, bumblebees consumed less pollen per day when fed EO exposed pollen compared to the no treatment control [28]. This likely contributed to slight differences in biomass and fat content between bees reared on sterile versus microberich provisions, though most pollen consumption occurs while fifth instar larvae in Osmia spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation